A case-control study of non-fatal traffic accidents on hospital patients in Bangkok metropolis - Dankmar Böhning (2018)
Morbidity and mortality from road traffic accidents in Bangkok metropolis is high with a trend strictly increasing in time, thus establishing one of the major public health problems and targets of the Kingdom of Thailand. An unmatched case-control study was undertaken to evaluate various risk patterns connected with the occurrence of traffic accidents 350 cases were sampled from five major hospitals distributed over the Bangkok Metropolitan area and 350 controls were included from out- patients of Rajawithi hospital. The major interest in this case-control analysis is to estimate relative risk (though odds ratio) and measure statistical significance of association between road traffic accident and the following risk factors: the demographic risk factors are age (age between 15 and 19 years has odds ratio of 8.25 [1.01, 67.72]; age above 40 is baseline), marital status (single has odds ratio of 2.74 [1.26, 5.95]; baseline is not- single), sex (males have an odds ratio of 2.05 [0.51, 8.24], occupation (salespersons have an odds ratio of 4.27 [1.47, 12.46]; baseline are office workers); the driving related exposure factors type of vehicle (motorbykers have an odds ratio of 6.22 [2.82, 13.78]; baseline are other vehicle drivers), driving time per day (odds ratio 1.35 [0.88, 2.09]) and the number of accidents in the last three years (odds ratio of 4.36 [2.51, 7.58]); the behavioral factors one hour before driving such as the consumption of alcohol (odds ratio 3.01 [1.53, 5.94]; baseline is no alcohol) and the consumption of a lot of food (odds ratio of 0.07 [0.03, 0.16]; baseline is not eating a lot before driving). The odds ratios for traffic accident when being under allergic medication and the consumption of tranquilizer were not significant. The results are consistent with current results in traffic accident research and point to target groups for potential prevention programmes in traffic accident prevention.